Room Temperature, Metal‐Free Arylation of Aliphatic Alcohols. Issue 2 (11th April 2014) - Ghosh, Raju; Lindstedt, Erik; Jalalian, Nazli; Olofsson, Berit
Abstract Diaryliodonium salts are demonstrated as efficient arylating agents of aliphatic alcohols under metal‐free conditions. The reaction proceeds at room temperature within 90 min to give alkyl aryl ethers in good to excellent yields. Aryl groups with electron‐withdrawing substituents are transferred most efficiently, and unsymmetric iodonium salts give chemoselective arylations. The methodology has been applied to the formal synthesis of butoxycaine.